Development of an individual warp beam tension control system for warp assembling machines in direct warp preparation - Recep Eren; Sinan Kılıç; Ömer Atalay (Journal of Engineered Fibers and Fabrics)
Warp preparation is a process prior to weaving that brings all the ends side by side and then winding them on a warp beam with the same tension and length at a predetermined width, density and length. Modern warp preparation machines employ feedback control systems controlling total or individual warp tension. Older warping machines in industry mostly do not have a precise feedback tension control systems and do not match with the quality requirements of today’s market expectations. This paper presents a research in which an individual section beam warp tension control system is explained for converting older beam-assembling machines to a new technology in a direct warping process. The total warp tension of each section warp beam was measured and breaking torque of the magnetic powder brake was adjusted when a deviation occured from the set tension value. It was shown that average loom efficiency increased by 5.65% despite an increase in average loom speed from 663 to 733 rpm in an air jet loom factory. The fabric fault ratio decreased from 3.45% to 1.04% per 100 m of fabric and warp waste decreased from 0.5% to below 0.2% with the new individual section warp beam tension control system adapted to an older version of the assembling machine having total tension control and section warp beam pneumatic brake system.